Seismic Multiattribute Application for Porosity Distribution at F3 Block, North Sea - Nurrochmah, Andryana Miftah; Herawati, Ida (UIR PRESS, 2024)
Reservoir characterization is essential in hydrocarbon exploration to understand subsurface properties, with porosity being a key indicator of storage capacity. This study focuses on mapping porosity in the FS8 interval of the F3 Block, North Sea, using a linear multi-attribute seismic approach. Post-stack seismic and well log data from four wells were utilized. A cross-plot of acoustic impedance (AI) and porosity logs shows a strong correlation, suggesting AI can be a useful attribute in the analysis. Acoustic impedance volumes were generated through model-based inversion, and a set of seismic attributes was selected using a stepwise regression method. The selected attributes—acoustic impedance, filtered impedance, amplitude envelope, and integrated absolute amplitude—were used to predict porosity values across the seismic volume. Cross-validation shows high correlation coefficients (training: 0.861; validation: 0.824) and low prediction errors (5.2% and 5.8%, respectively), indicating robust prediction accuracy. The resulting porosity distribution map reveals a spatial trend, with higher porosity in the shallower western area and lower porosity in the deeper eastern area.